2005
DOI: 10.1111/j.1525-1470.2005.00106.x
|View full text |Cite
|
Sign up to set email alerts
|

Focal Dermal Hypoplasia with Exuberant Fat Herniations and Skeletal Deformities

Abstract: Focal dermal hypoplasia or Goltz syndrome is a rare congenital and mesoectodermal dysplasia with multisystemic involvement. Although the genetic alterations responsible for focal dermal hypoplasia are not fully known, there is predominance in affected females, suggesting dominant X-linked inheritance. Besides the skin, other structures frequently involved are the skeletal system, eyes, teeth, hair, and nails. Skeletal abnormalities are predominantly observed in the hands and feet. We report a 9-year-old girl w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…3,4 It is characterized primarily by extensive cutaneous abnormalities, including fat herniating through dermal defects and forming hyperpigmented papillomas. 5 A comprehensive review of the literature in 1992 identified 200 cases worldwide and expanded the clinical syndrome to include malformations of the ocular, craniofacial, and musculoskeletal systems.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 It is characterized primarily by extensive cutaneous abnormalities, including fat herniating through dermal defects and forming hyperpigmented papillomas. 5 A comprehensive review of the literature in 1992 identified 200 cases worldwide and expanded the clinical syndrome to include malformations of the ocular, craniofacial, and musculoskeletal systems.…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal wall defects, diaphragmatic hernias and renal abnormalities have also been reported. Histology is characterised by markedly thinned dermis 2 3. The genetic defect has been identified as mutation in PORCN gene (Xp11.23) 4.…”
Section: Discussionmentioning
confidence: 99%
“…These nodules were the herniation of adipose cells through dermal defects and nodules will become lipomatous tumors (Miranda et al, 2005). This finding has been referred to as "fat herniation" and reported in more than %50 of cases.…”
Section: Discussionmentioning
confidence: 99%